KERAGAAN PERTUMBUHAN DAN HASIL 20 GENOTIPE CABAI MERAH (Capsicum annuum L.) DI DATARAN RENDAH - Viona Juanda Putri; Catur Herison; Merakati Handajaningsih; Marulak Simarmata; Rustikawati; Sukisno (BPFP Universitas Bengkulu, 2025)
[GROWTH ADAPTATION AND PRODUCTIVITY OF 20 CAYENNE PEPPERS (Capsicum annuum L.) GENOTYPES IN LOWLANDS AREA]. The cultivation of chili peppers in lowland areas of Indonesia faces several environmental challenges. Efforts to increase red chili production in lowland regions include planting genotypes that are adaptive to local environmental conditions. This study aims to obtain information on the best red chili genotypes that can adapt and produce well in lowland areas. The research was conducted from May 2024 to September 2024 using the Completely Randomized Block Design (CRBD) method with a single-factor treatment, consisting of 20 genotypes red chili with three replications. The data collected included growth variables (plant height, first dichotomous height, leaf area, number of dichotomous points, stem diameter, and plant dry biomass) and yield variables (first harvest age, number of fruits per plant, fruit diameter, fruit length, fruit weight per plant, and percentage of marketable fruit). The results showed that the ‘Lotanbar’ genotype exhibited the best performance during the vegetative phase, as indicated by the largest total leaf area, the highest number of dichotomous points, the largest stem diameter, and the highest plant dry weight compared to other genotypes. Meanwhile, the ‘Baja F1’ genotype demonstrated superior performance during the generative phase, producing the largest fruit diameter and the highest fruit weight per plant, reaching up to 200% higher than the genotype with the lowest yield. Thus, the ‘Lotanbar’ genotype is recommended for optimization during the vegetative growth phase, while ‘Baja F1’ is more ideal for increasing yield during the generative phase in red chili cultivation in lowland areas.